2008
DOI: 10.1123/jsep.30.4.353
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Goal Content for Exercise Questionnaire

Abstract: Self-determination theory (SDT; Deci & Ryan, 2000) proposes that intrinsic, relative to extrinsic, goal content is a critical predictor of the quality of an individual's behavior and psychological well-being. Through three studies, we developed and psychometrically tested a measure of intrinsic and extrinsic goal content in the exercise context: the Goal Content for Exercise Questionnaire (GCEQ). In adults, exploratory (N = 354; Study 1) and confirmatory factor analyses (N = 312; Study 2) supported a 20-item s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
111
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 64 publications
4
111
2
2
Order By: Relevance
“…In this sense, Sebire, Standage and Vansteenkiste (2008) suggested that it is the goal content (motives) that is the major impetus for the individuals' behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this sense, Sebire, Standage and Vansteenkiste (2008) suggested that it is the goal content (motives) that is the major impetus for the individuals' behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The goal content theory makes a distinction between intrinsic and extrinsic goals, as well as analysing its impact on motivation regulation and wellbeing (Sebire et al, 2008). According to the authors, the goals are then viewed according to the way they can provide satisfaction of the three basic psychological needs (autonomy, competence, and relatedness) and they have a differentiated impact on the individuals' wellbeing, taking into consideration their content (intrinsic or extrinsic).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations